Meningkatkan Pemahaman Konsep IPA Melalui Metode Demonstrasi Di Kelas VB SDN 61/X Talang Babat - Deni Sulistiowati Ningsih (Jurnal Gentala Pendidikan Dasar, 2019)
Abstract. This research is a classroom action research that aims to improve the understanding of the science concept. The subject of this study was Vb grade students of SDN 61 / X Talang Babat. This classroom action research was carried out in two cycles. At the beginning of the first cycle, a plan is made to make the lesson plan, the second step is to implement RPP, the observer records the course of the implementation of the first cycle on the observation sheet, the observation results are reflected and set out in the reflection sheet. At the end of the first cycle evaluation was carried out with results that had increased from the pre-cycle activities. The results of the learning evaluation are converted into a table of results of understanding the concept, the results of the conversion state that the research has not yet reached the target, it needs to be continued with the second cycle. The evaluation results of the second cycle were converted to a conceptual understanding table of students, where in the conversion table it was illustrated that the research had reached the target. Comparison of evaluation results from the first cycle with the second cycle there was an increase of 13%. The results of the comparison state that the demonstration method can improve concept understanding of students of SDN 61 / X Talang Babat in class VB. Keywords: Understanding Concepts, IPA, demonstration methods